East African Community Law Institutional, Substantive and Comparative EU Aspects - Ugirashebuja, Emmanuel; Ruhangisa, John; Ottervanger, Tom; Cuyvers, Armin (Brill, 2017)
Written by leading experts in EAC and EU law, including the President of the EACJ, East African Community Law is the first comprehensive and open-access text book on EAC law which also provides a systemic comparison with the EU. Readership: All interested in East African Law, European Law, International Law, Comparative Law and Human Rights.